SARS-CoV-2 transmission risk from sports equipment (STRIKE) - Edwards, T.; Kay, G. A.; Aljayyoussi, G.; Owen, S. I.; Harland, A. R.; Pierce, N. S.; Calder, J. D. F.; Fletcher, T. E.; Adams, E. R. (Scientific Reports, 2021)
OBJECTIVES To investigate the potential of shared sporting equipment as transmission vectors of SARS-CoV-2 during the reintroduction of sports such as soccer, rugby, cricket, tennis, golf and gymnastics. SETTING Laboratory based live SARS-CoV-2 virus study INTERVENTIONS Ten different types of sporting equipment were inoculated with 40µl droplets containing clinically relevant high and low concentrations of live SARS-CoV-2 virus. Materials were then swabbed at time points relevant to sports (1, 5, 15, 30, 90 minutes). The amount of live SARS-CoV-2 recovered at each time point was enumerated using viral plaque assays, and viral decay and half-life was estimated through fitting linear models to log transformed data from each material. MAIN OUTCOME MEASURE The primary outcome measure was quantification of retrievable SARS-CoV-2 virus from each piece of equipment at pre-determined time points. RESULTS At one minute, SARS-CoV-2 virus was recovered in only seven of the ten types of equipment with the low dose inoculum, one at five minutes and none at 15 minutes. Retrievable virus dropped significantly for all materials tested using the high dose inoculum with mean recovery of virus falling to 0.74% at 1 minute, 0.39% at 15 minutes and 0.003% at 90 minutes. Viral recovery, predicted decay, and half-life varied between materials with porous surfaces limiting virus transmission. CONCLUSIONS This study shows that there is an exponential reduction in SARS-CoV-2 recoverable from a range of sports equipment after a short time period, and virus is less transferrable from materials such as a tennis ball, red cricket ball and cricket glove. Given this rapid loss of viral load and the fact that transmission requires a significant inoculum to be transferred from equipment to the mucous membranes of another individual it seems unlikely that sports equipment is a major cause for transmission of SARS-CoV-2. These findings have important policy implications in the context of the pandemic and may promote other infection control measures in sports to reduce the risk of SARS-CoV-2 transmission and urge sports equipment manufacturers to identify surfaces that may or may not be likely to retain transferable virus.